Versatility of bilayer metal oxide coatings on silver nanowire networks for enhanced stability with minimal transparency loss. Issue 42 (11th October 2019) - Aghazadehchors, Sara; Nguyen, Viet Huong; Muñoz-Rojas, David; Jiménez, Carmen; Rapenne, Laetitia; Nguyen, Ngoc Duy; Bellet, Daniel
Abstract : Silver nanowire (AgNW) networks have been lately much investigated thanks to their physical properties and are therefore foreseen to play a key role in many industrial devices as transparent electrodes, but their stability can be an issue. Abstract : Silver nanowire (AgNW) networks have been lately much investigated thanks to their physical properties and are therefore foreseen to play a key role in many industrial devices as transparent electrodes, but their stability can be an issue. Although it has been shown that thin metal oxide coatings enhance the stability of AgNW networks, such stabilization is achieved at the expense of transparency. We demonstrate that by depositing a second oxide coating, which acts as an antireflective layer, it is possible to obtain highly stable and transparent composite electrodes. AgNW networks were deposited by the airbrush method, and zinc oxide (ZnO) and aluminum oxide (Al2 O3 ) coatings were deposited, by Atmospheric Pressure Spatial Atomic Layer Deposition (AP-SALD), using both glass and plastic substrates; therefore, the proposed fabrication method is low-cost and compatible with high-throughput scalable fabrication. The mechanical stability of bare, ZnO and ZnO/Al2 O3 -coated AgNWs upon bending is also presented. The obtained nanocomposites exhibit highly homogeneous and conformal oxide coatings with average thicknesses of a few tens of nanometers. Samples with bilayer coatings of 70 nm ZnO/70 nm Al2 O3 still exhibit very good stability after annealing in air up to 450 °C for 6 repetitive cycles.